Possibility of Using Fuel Cells for Co-generation of Heat and Power in Venizelio Hospital in Crete, Greece - Vourdoubas, John (Environmental Management and Sustainable Development, 2022)
Mitigation of climate change requires the replacement of traditional energy technologies with novel low carbon energy systems. The possibility of using a fuel cell and a hybrid energy system consisted of a fuel cell and solar-PV panel for energy generation in Venizelio hospital located in Crete, Greece has been investigated. The size, the heat and electricity generated, the H2 required and the capital cost of the fuel cell and the solar-PV system covering the energy requirements in the hospital have been estimated. Existing research has indicated that fuel cells using H2 can cover the heat and electricity needs in various buildings. Our results indicated that a fuel cell at 1 397 KW can produce annually 4 895 MWhel and 4 895 MWhth covering all the electricity and heating needs in Venizelio hospital producing excess heat at 2 451 MWhth. The capital cost of the fuel cell has been calculated at 4 191 000 € while the required H2 at 367.5 tons/year. All the energy requirements of the hospital can be also covered with a hybrid energy system consisted of a fuel cell and a solar-PV system. The size of the fuel cell has been estimated at 697.5 KW and the cost at 2 092 500 €. The electricity generation was at 2 444 KWhel and its heat production at 2 444 KWhth. The size of the solar-PV system has been evaluated at 1 629 KWp and the cost at 1 634 000 €.The annual electricity generation was at 2 451 MWhel. The capital cost of the hybrid energy system at 3 726 500 € is lower than the cost of the fuel cell alone at 4 191 000 €. Our results indicated that the use of novel benign energy systems with zero carbon emissions in Venizelio hospital is technically and economically feasible.